Fission hindrances in transfermium nuclei - Lopez-Martens A.; Hauschild K.; Svirikhin A.I.; Asfari Z.; Chelnokov M.L; Chepigin V.I.; Dorvaux O.; Forge M.; Gall B.; Isaev A.V.; Izosimov I.N.; Kessaci K.; et al. (EPJ Web of Conferences, 2023)
Very heavy nuclei owe their stability against spontaneous fission to quantum shell effects, which depend on the local density of single-particle states. The height but also the width and the structure of the barrier in multi-dimensional deformation space determine the fission half-lives. Other effects come into play, such as the conservation of quantum numbers and superfluidity or stiffness of the system in the fission process. This is why odd nuclei have longer fission partial half-lives with respect to their even neighbours and also why multi-quasi-particle states, such as high-K states, are thought to be more stable against fission than the ground state. We will report here on two different fission studies carried out with the GABRIELA detector array at the focal plane of the recoil separator SHELS. The first study concerns the fission properties of 253Rf, the most neutron deficient Rf isotope known to date. The second study focusses on a new measurement of the fission hindrance of the known 8- isomer in 254No.